The narrative perspective of "The Granada Trilogy" novel by Radwa Ashour - Hossein Mohtadi; Fatamah Abdollah-Youssof; Mofid Qomaheh (دراسات في اللغة العربيّة وآدابها)
In this article, we will dedicate the discourse on the structure of the site, and both the ideological and psychological levels related to the “Granada Trilogy”, showing the author's brilliant thought and ambitious spirit, and shedding light on the importance of that through what the characters say, as given by the narrators. In light of the previously analyzed positions of the narrators in the “Trilogy”, it becomes explicit to us that the author focuses on a knowledgeable narrator who is present and absent at the same time. However, the latter is more often present in the novel. That is, the ideological level in the trilogy was represented by several axes, such as religion, politics, society, and history, all of which were linked to each other to form the narrative text that was crystallized with a fascinating thought. Hence, the author seemed aware and broadly cultured of the history of the Arab world, as the present is nothing but an extension of the past since research in the past helps the recipient understand his present, and to preserve his entity and his Arab identity from any rape or assault. Indeed, this is what the novelist aimed for as she derived from historical events a contemporary intellectual and artistic vision to serve its political, social, and religious goals. From a sociological perspective, what we have seen in the novel by “Radwa Ashour” represents being aware of the events and the ongoing conflict in Granada, which is symbolized by Palestine today, about identity and land. This stems from a conscious culture and mature thought, which made its narrative a confidently-paced vision, related to the environment and the society she was born in. Altogether, those aspects formed a psychological obsession with how to preserve it, and expel every occupier and usurper of the land. Thereupon, in this study, we relied on the structural-formal approach because the “Granada Trilogy” narrates psychological, social, and intellectual pain.